Unlocking the Tourism Potential of Londo Dam: Strategic Branding for Community Development: Membuka Potensi Wisata Dam Londo: Pencitraan Merek Strategis untuk Pengembangan Masyarakat - Satrio Sudarso; Akbar Rahmadin; Hilda Halimah Hanum; Putri Juni Alita Dwi Bastari; Ahmad Reza Rahmawan (Proceedings of The ICECRS, 2024)
General Background The expansion of leisure sectors serves as an essential instrument for regional progress and local economic empowerment. Specific Background A historical leisure site in Seloliman village possesses significant natural assets but remains largely unrecognized by broader domestic audiences due to declining visitor numbers. Knowledge Gap Despite widespread technological adoption globally, local rural destinations often lack comprehensive digital information systems and promotional platforms to attract modern travelers. Aims This study formulates and implements an integrated promotional strategy utilizing digital and visual platforms to elevate destination recognition and rural prosperity. Results The qualitative intervention successfully delivered a cinematic promotional video, an interactive website, stage banners, and barcode-integrated physical posters. These coordinated efforts provided accurate site information, heightened traveler awareness, and positively contributed to local financial income. Novelty This research demonstrates the synergistic application of synchronized physical and online promotional materials specifically tailored for rural heritage site recovery. Implications Rural stakeholders must adopt continuous social networking management and unified promotional strategies, including the potential appointment of local ambassadors, to sustain visitor visibility and continuous financial growth. Highlights: Creating cinematic promotional videos and interactive websites significantly raises visitor awareness for rural destinations. Deploying barcode-integrated posters and physical banners successfully delivers vital site information to travelers. Integrating online promotions and physical marketing materials directly supports local village economic revitalization. Keywords: Digital Promotion, Heritage Site, Local Income, Visual Media, Promotional Strategy